INSURANCE ORGANIZATIONS FINANCIAL RISKS ASSESSMENT METHODS (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This Article Notes The Relevance Of The Formation Of Conceptual Approaches To The Assessment Of Financial Risks, Examines The Issue Of Their Direct Or Indirect Impact On The Results Of Financial Activities Of Subjects. In Particular, It Is Indicated That The Main Task Of Risk Management Is The Assessment And Analysis Of Probabilistic Risk, The Choice Of Methods To Minimize Risk By Identifying Its Factors. The Author Presents Modern Methods Of Assessing The Level Of Financial Risk, As Well As The Necessary Methodological Manuals For Determining The Level Of Profitability Of Financial Transactions On The Example Of Insurance Organizations In Uzbekistan. This Approach To The Formation Of The Necessary Level Of Profitability Of Financial Transactions, Taking Into Account Risk Factors, Allows For The Interconnection Of Indicators In The Process Of Financial Activity Of Insurance Organizations As A Whole.